Answer:
100 point sheeshhh ill take em but i don't have awnsers m8
the derivative of the function would be
d/dx=−y/x2∗1/(1+(y/x)2)
= -yx^-2
Answer:
one solution
Step-by-step explanation:
3 -2x=5-x+3+4x
Combine like terms
3-2x = 8+3x
Add 2x to each side
3-2x+2x = 8+3x+2x
3 = 8+5x
Subtract 8 from each side
3-8 =8+5x-8
-5 =5x
Divide by 5
-5/5 = 5x/5
-1 =x
There is one solution
Answer:
y= 4/3
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
−2=3(y−2)
−2=(3)(y)+(3)(−2)(Distribute)
−2=3y+−6
−2=3y−6
Step 2: Flip the equation.
3y−6=−2
Step 3: Add 6 to both sides.
3y−6+6=−2+6
3y=4
Step 4: Divide both sides by 3.
3y
/3
=
4
/3
y=
4/3
Answer:
y=
4/3
Ok so the first thing to do would be get rid of the fraction. To do that multiply the ENTIRE equation but the denominator. Once all the numbers are multiplyed I think it’ll be easier for u to solve them :) or if u wanna solve them quick, download Photomath :)